2015
DOI: 10.4236/aim.2015.56041
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Herpes Simplex Virus in Pregnant Women from Gangetic Plain Region of Allahabad, India

Abstract: Herpes Simplex Virus (HSV) is a common pathogen that leads to lifelong latent infection and may be associated with transmission from mother to their fetus. A total of 191 blood samples of pregnant women were collected to check the prevalence of Herpes Simplex Virus (HSV). It was observed that 124 (64.9%) and 04 (2.1%) samples were positive for HSV IgG and HSV IgM, respectively. Seropositivity of HSV IgG was the highest for third trimester and it was followed by second and first trimester; while it was the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…It could contribute to the high prevalence observed which is in agreement with the previous studies reported by 14,40 While in India inconsistent published by. 29 In our study, there was a significant association between education level and HSV-2 seropositivity. This finding similar to some studies.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It could contribute to the high prevalence observed which is in agreement with the previous studies reported by 14,40 While in India inconsistent published by. 29 In our study, there was a significant association between education level and HSV-2 seropositivity. This finding similar to some studies.…”
Section: Discussionsupporting
confidence: 52%
“…25 Regarding the high level of HSV-2 IgG, seropositivity was reported also by other countries researchers such as in Saudi Arabia 27.1% (9), Sudan 34.6%, 63.3%, 91.1%. 26 Iraq 22.2%, 27 Syria 52%, 28 India 64.9%, 34.86%, 29 Ethiopia 32.1%, 30 Nigeria 82.2%,33.3%, 13,31 Ghana 78.3 %, 32 Zimbabwe 49.1%, 51.10%, 33,34 Eastern Nepal 35.8 %, 35 Cote D'ivoire 96.5%, 36 Germany 82%, 37 Switzerland 21.2%, 38 Brazil 15.6% 39 and USA 22%. 10 These shades as mentioned above showed higher findings in terms of the rate of HSV-2 IgG infection.…”
Section: Discussionmentioning
confidence: 99%
“…25 While, Mohammad and Salman showed a maximum rate of HSV-2 infection at second trimester, 26 and Amar et al (2015) in India showed that the seropositivity of IgM were 3.3% in the first, and 1.1% in the second trimester. 27 The prevalence of HSV-2 IgG, IgM antibody among women who have had a history of abortion was not significant (p value>0.05) compared to women without a history of abortion. These finding was not in line with Assayaghi et al…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, the prevalence of HSV 1 and 2 infection in pregnant women was 42.4%. High seroprevalence of 57-64% for HSV in India was reported by few studies [ 2 , 19 , 27 , 28 ]. But in developed nations, HSV seroprevalence is estimated to be around 7-22% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%